News-driven international credit cycles - G. Kemal Ozhan (Bank of Canada, 2021)
How does news about future economic fundamentals affect within-country and cross-country credit allocation? How effective is unconventional policy when financial crises are driven by unfulfilled favorable news? I study these questions by employing a two-sector, two-country macroeconomic model with a financial sector in which financial crises are associated with occasionally binding leverage constraints. In response to positive news on the valuation of nontraded sector capital that turns out to be incorrect at a later date, the model captures the patterns of financial flows and current account dynamics in Spain between 2000-2010, including the changes in the sectoral allocation of bank credit and movements in cross-country borrowing during the boom and the bust. When there are unconventional policies by a common authority in response to unfulfilled favorable news, liquidity injections perform better in ameliorating the downturn than direct assets purchases from the non-traded sector.
Keywords: E44; F32; F41; G15; G21; 330; Credit and credit aggregates; Economic models; Financial stability; Sectoral balance sheet; Recent economic and financial developments